Burden of pneumococcal community-acquired pneumonia in adults across Europe: A literature review. (April 2018) - Torres, Antoni; Cillóniz, Catia; Blasi, Francesco; Chalmers, James D.; Gaillat, Jacques; Dartois, Nathalie; Schmitt, Heinz-Josef; Welte, Tobias
Abstract: Background: The burden of community-acquired pneumonia (CAP) caused by Streptococcus pneumoniae (pneumococcus) among adults in Europe is poorly defined. Methods: Structured searches of PubMed were conducted to identify the incidence of pneumococcal CAP among adults across Europe. Results: The overall incidence rates for CAP was 68–7000 per 100, 000 and the incidence in hospitalised CAP cases of all causes was 16–3581 per 100, 000. In general the incidence of CAP increased consistently with age. Available data indicated higher burdens of pneumococcal CAP caused in groups with more comorbidities. Most cases of pneumococcal CAP (30%–78%) were caused by serotypes covered by PCV13 vaccine; the incidence of PCV13-related pneumonia decreased after the introduction of childhood vaccination. Conclusions: We observed a high burden adult pneumococcal CAP in Europe despite use of the 23-valent pneumococcal polysaccharide vaccine, particularly in elderly patients with comorbidities. CAP surveillance presented wide variations across Europe. Pneumococcal CAP has to be monitored very carefully due to the possible effect of current vaccination strategies. Highlights: The data available demonstrate the significant burden of pneumococcal CAP in European adults, especially in the elderly. Pneumococcal CAP in the elderly increases the risk of mortality three-fold compared with non-pneumococcal CAP. Pneumococcal CAP has to be monitored very carefully, due to the possible effects of current vaccination strategies.